Dielectric Permittivity, Loss Factor and Ac. Conductivity of (Epoxy / Ferrous Sulfide) Composites. - Hussain , Waleed. (University of Thi-Qar Journal of Science, 2015)
The dielectric properties of (Epoxy/Ferrous sulfide) composites were characterized as a function of Ferroussulfide weight fraction, temperature was in the range 30-150  o C, and frequency was in range 120 Hz -2MHz . Thedielectric parameters have been measured using parallel plate capacitor method. Experimental results showed that the real ε' and imaginary ε" parts of permittivity increases as Ferrous sulfide weight fraction increases. The values of ε' increase as the temperature increases, the increase was accompanied by the presence of obvious peaks at high temperature which may be related to the increased mobility of segments of epoxy molecules at elevated temperatures below the glass-transition temperature and the differential thermal expansion of the polymer and the filler. The values of ε' decrease as frequency increases, which indicates that the major contribution to polarization is related to orientation polarization. Dielectric loss showed an increase both with an increase in frequency and temperature, loss peaks were observed at 10 kHz and at high temperatures respectively. A.c conductivity and impedance behaviors of the composites as a function of temperature and frequency were investigated too.